Islamic History of Animal Welfare and Status of Cat in Islam - Sarwar, Dr. Muhammad; Shahzad, Aamir (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
This article explores the Islamic teachings and historical practices concerning animal welfare, with a special focus on the status of cats in Islamic tradition. Drawing from primary sources including the Qur’an, Hadith literature, and classical Islamic jurisprudence, the study highlights the compassionate principles embedded within Islamic teachings. The research also sheds light on how early Muslim societies interacted with animals—particularly cats—and their significance in religious and cultural contexts. The article concludes that Islam advocates for the ethical treatment of animals and holds cats in particularly high regard due to their cleanliness, independence, and documented presence in the life of Prophet Muhammad (PBUH). By exploring Islamic perspectives, researchers and policymakers can engage religious communities in meaningful dialogue around animal ethics. Studies have also shown that faith-based approaches to animal welfare can be more culturally effective in Muslim-majority contexts than secular models alone. This comprehensive mercy implies that human beings are obligated to extend compassionate treatment toward all creatures, including animals. Islamic law prohibits unnecessary harm, overburdening, or abuse of animals. It mandates proper feeding, medical care when needed, and humane treatment. For example, animals used for labor must not be overworked or beaten. Organizations in countries like Turkey, Pakistan, and Indonesia have integrated Islamic principles into their efforts to protect and care for animals. Religious leaders have emphasized the importance of treating animals with dignity, often using sermons and fatwas to raise awareness of the ethical obligation to care for all creatures. Islamic art and literature, from Persian miniatures to Ottoman ceramics and Rumi’s poetry, have celebrated cats as symbols of beauty, grace, and intelligence.